1997
DOI: 10.1083/jcb.137.5.1091
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of the Pemphigus Vulgaris Antigen (Desmoglein 3) Gene in Mice Causes Loss of Keratinocyte Cell Adhesion with a Phenotype Similar to Pemphigus Vulgaris

Abstract: In patients with pemphigus vulgaris (PV), autoantibodies against desmoglein 3 (Dsg3) cause loss of cell–cell adhesion of keratinocytes in the basal and immediate suprabasal layers of stratified squamous epithelia. The pathology, at least partially, may depend on protease release from keratinocytes, but might also result from antibodies interfering with an adhesion function of Dsg3. However, a direct role of desmogleins in cell adhesion has not been shown. To test whether Dsg3 mediates adhesion, we genetically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
366
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(387 citation statements)
references
References 60 publications
19
366
0
2
Order By: Relevance
“…In contrast, DSC3 ablation resulted in preimplantation lethality, suggesting a desmosome-independent role during early development (Den et al 2006). Similarly, ablation of DSG isotypes revealed distinct functions in vivo: Whereas the DSG2 KO was embryonic lethal (Eshkind et al 2002), DSG3 KO mice showed weakened desmosomal adhesion, leading to the separation of keratinocytes (Koch et al 1997). The loss of DSG1 function has so far not been analyzed in mice as it requires deletion of all three DSG1 genes.…”
Section: Evidence From Mouse Models and Human Diseasesmentioning
confidence: 99%
“…In contrast, DSC3 ablation resulted in preimplantation lethality, suggesting a desmosome-independent role during early development (Den et al 2006). Similarly, ablation of DSG isotypes revealed distinct functions in vivo: Whereas the DSG2 KO was embryonic lethal (Eshkind et al 2002), DSG3 KO mice showed weakened desmosomal adhesion, leading to the separation of keratinocytes (Koch et al 1997). The loss of DSG1 function has so far not been analyzed in mice as it requires deletion of all three DSG1 genes.…”
Section: Evidence From Mouse Models and Human Diseasesmentioning
confidence: 99%
“…The desmosomal cadherins (DCs), of which there are seven in humans, three desmocollins (Dsc1 -3) and four desmogleins (Dsg1-4), are membrane-spanning adhesion molecules of desmosomes. Genetic ablation of Dsc1 and Dsg3 results in epidermal blistering in transgenic mice, illustrating the importance of these molecules for the maintenance of normal intercellular adhesion (Koch et al, 1997;Chidgey et al, 2001). Loss of expression of DCs has been documented in various cancers (see Chidgey, 2002;Biedermann et al, 2005;Oshiro et al, 2005) and overexpression of DCs in nonadhesive cultured fibroblasts generates adhesion and inhibits invasion (Tselepis et al, 1998), supporting the idea that DCs have a tumour suppressor role.…”
mentioning
confidence: 94%
“…In 1997, Koch et al reported the first targeted ablation of a desmosomal cadherin, Dsg3, which is allelic to the naturally occurring balding mouse [8]. Dsg3 knockout mice are runted, display hair loss due to failure of telogen club hair anchorage, and recapitulate many of the aspects of the autoimmune disease pemphigus vulgaris such as oral blistering.…”
Section: Lessons From Human Skin and Heart Diseases And Mutant Animalmentioning
confidence: 99%